ANALISIS KARAKTER INTRAPRENEUR PADA MAHASISWA CORPORATE ENTREPRENEUR UNIVERSITAS CIPUTRA - Junko Alessandro Effendy (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The purpose of this study is to find out what intrapreneur spirits are formed after the learning process at the Ciputra University corporate entrepreneurship guild. The respondents from this research are 55 students from corporate entrepreneurship guild. The research approach used confirmatory factor analysis. Researchers used six variables, namely innovativeness, opportunity recognition, risk taking, authentic leadership, pro-active and persistent. The results showed that of the six variables used, it was found that five variables reflected the intrapreneur spirit of corporate entrepreneurship guild students, namely innovativeness, opportunity recognition, authentic leadership, pro-active and persistent. The risk taking variable did not reflect the intrapreneur spirit of the Ciputra University student corporate entrepreneurship